B cell subsets in atherosclerosis - Perry, Heather M.; Bender, Timothy P.; McNamara, Coleen A. (Frontiers in Immunology, 2012)
Atherosclerosis, the underlying cause of heart attacks and strokes, is a chronic inflammatory disease of the artery wall. Immune cells, including lymphocytes modulate atherosclerotic lesion development through interconnected mechanisms. Elegant studies over the past decades have begun to unravel a role for B cells in atherosclerosis. Recent findings provide evidence that B cell effects on atherosclerosis may be subset-dependent. B-1a B cells have been reported to protect from atherosclerosis by secretion of natural IgM antibodies. Conventional B-2 B cells can promote atherosclerosis through less clearly defined mechanism that may involve CD4 T cells. Yet, there may be other populations of B cells within these subsets with different phenotypes altering their impact on atherosclerosis. Additionally, the role of B cell subsets in atherosclerosis may depend on their environmental niche and/or the stage of atherogenesis. This review will highlight key findings in the evolving field of B cells and atherosclerosis and touch on the potential and importance of translating these findings to human disease.